Evaluasi Kebijakan Peraturan Majelis Dikdasmen Muhammadiyah tentang Kinerja Guru Di SMA Muhammadiyah 1 Gresik - Faizah, Any (Program Studi Magister Pedagogi, 2014)
Any FaizahGuru Biologi SMA Muhammadiyah 1 Gresik.e-mail: anyfaizah69@yahoo.co.idAbstract:The approach used in this research is a qualitative approach using observation, questionnaires, interviews and documentation as the instruments of data collection. The results of this research showed that the regulation of Muhammadiyah Regional Leadership Council of Primary and Secondary Education about teachers’ performance is proved effective in the implementation at State Senior High School of Muhammadiyah 1 Gresik. The implementation of regulation on teachers’ performance assessment in State Senior High School of Muhammadiyah 1 Gresik addressed with full readiness, and dedicated in accordance with their each field. The effectiveness was shown from the values of performance achieved by teachers of State Senior High School of Muhammadiyah 1 Gresik, which obtain an average